2011
DOI: 10.1038/nature10715
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of TRPA1 thermal sensitivity enables sensory discrimination in Drosophila

Abstract: Discriminating among sensory stimuli is critical for animal survival. This discrimination is particularly essential when evaluating whether a stimulus is noxious or innocuous. From insects to humans, TRP channels are key transducers of thermal, chemical and other sensory cues1, 2. Many TRPs are multi-modal receptors that respond to diverse stimuli1–3, but how animals distinguish sensory inputs activating the same TRP is largely unknown. Here we determine how stimuli activating Drosophila TRPA1 are discriminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
279
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(300 citation statements)
references
References 33 publications
(71 reference statements)
20
279
0
1
Order By: Relevance
“…We found that ectopic expression of these H 2 O 2 -sensitive dTRPA1 isoforms conferred UV sensitivity to light-insensitive cultured HEK293 cells and a few types of light-insensitive Drosophila neurons. The light and H 2 O 2 sensitivities are specific to certain dTRPA1 isoforms, consistent with previous findings that different dTRPA1 isoforms exhibit distinct thermal sensitivities (20,21). Strikingly, the H 2 O 2 -sensitive dTRPA1 was as effective as channelrhodopsin-2 (ChR2) in triggering light-produced motor responses when expressed in a specific group of motor neurons that control proboscis extension…”
supporting
confidence: 89%
See 3 more Smart Citations
“…We found that ectopic expression of these H 2 O 2 -sensitive dTRPA1 isoforms conferred UV sensitivity to light-insensitive cultured HEK293 cells and a few types of light-insensitive Drosophila neurons. The light and H 2 O 2 sensitivities are specific to certain dTRPA1 isoforms, consistent with previous findings that different dTRPA1 isoforms exhibit distinct thermal sensitivities (20,21). Strikingly, the H 2 O 2 -sensitive dTRPA1 was as effective as channelrhodopsin-2 (ChR2) in triggering light-produced motor responses when expressed in a specific group of motor neurons that control proboscis extension…”
supporting
confidence: 89%
“…Animals were raised in standard molasses/cornmeal/yeast/agar food and maintained in a Darwin Chamber with temperature set at 25°C and humidity level at 60-65%. The stocks used were as follows: w 1118 , UAS-GCaMP3 (BL-32236), UAS-GCaMP6 (BL-42746), UAS-ChR2-YFP, E49-GAL4 (31), AKH-GAL4 (BL-25684), dTRPA1 KO (27), Gr28b PBac01884 (BL-10743), Gr28b Df(2L)7031 /CyO (BL-7804), norpA 36 (BL-9048), santa-maria (BL-24520), UAS-dTRPA1-RNAi (27), UAS-DUOX-RNAi 1 (BL-32903), UAS-cat (BL-24621), ILP7-GAL4 (44), UAS-dTRPA1(A)10b (21), UAS-dTRPA1(B)10a (20), ppk1-GAL4 (45), UAS-dTRPA1(A)10a (this work), UAS-mTRPA1 (a gift from J. Grandl, Department of Neurobiology, Duke University, Durham, NC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…How does the same channel distinguish different types of stimuli? At least in Drosophila, this is achieved through alternative exon usage (Kang et al 2012). Chemosensory and thermosensitive TRPA1 channels arise from distinct isoforms that contain different N-terminal sequences.…”
mentioning
confidence: 99%